Réponses

2014-01-22T22:12:15+01:00
A) 6(-4x-5)+7 = -24x-30+7
                   = -24x-23

b) -5(6-4y)-5y= -30+20y-5y
                   = -30+15y

c) 5(-2a+7)+3a= -10a+35+3a
                     = -7a+35

d) 3b(5-6b)-9b = 15b-18b²-9b
                     = -18b²+6b
je te remerci mais je crois que tu n'a pas compris la consigne ^^
2014-01-22T22:42:22+01:00
A) 6(-4X-5)+7 = -24X-30+7= -24X-23

b)-5(6-4Y)-5Y = -30+20Y-5Y= -30 - 15Y = 15(-2-Y)

c) 5(-2a+7)+3a= -10a+358+3a=-7a+35 = 7(-a+5)

d) 3b(5-6b)-9b=15b-18b²-9b=6b-18b²=6b(1-3b)

C'est mieux?